A study on assessment of sleep quality in south Indian pregnant women - Venugopal, Lalitha; Rajendran, Priyadharsini; V., Parghavi (International Journal of Research in Medical Sciences, 2018)
Background: Sleep disturbances are common during pregnancy. The risk of sleep disturbances is estimated to be two times higher in the later part of pregnancy compared to the early trimester. Thus, the present study was planned to assess the sleep quality in different trimesters of South Indian pregnant women. Methods: This was a descriptive cross-sectional questionnaire-based study. A total of 90 healthy pregnant women with a mean age of 25 years were recruited and sleep quality was assessed using a standardized PSQI questionnaire. Mean global PSQI score of ≥5 is suggestive of poor sleep quality. A p value <0.05 was considered statistically significant. Results: Subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleeping medications and daytime medication were found to be significantly higher in the second and third trimester (p<0.0001) pregnant women. Mean global PSQI score was ≥5 in the third trimester pregnant women. Conclusions: The present study shows that the sleep quality is disturbed during pregnancy and it is more in the third trimester of pregnancy. Pregnant women should be aware of the effects of sleep deprivation and adverse outcomes related to it. Thus, proper identification of sleep disturbances and a good awareness on the cumulative effects of the risk factors associated with sleep deprivation during pregnancy will help the physicians to manage and prevent the adverse maternal and fetal outcomes.